Reinterpreting Aristotle in light of neo-Aristotelians: Function, Friendship, and Self-Knowledge - Çetinkaya, Janset Özün (2023)
This thesis offers three novel accounts on three different topics that fall under Aristotle’s account of happiness and flourishing.